Mana Tangatarua
1 online resource (xv, 287 pages)
Keywords: "This volume explores mixed race/mixed ethnic identities in Aotearoa/New Zealand. Mixed race and mixed ethnic identity are growing in popularity as research topics around the world. This edited collection looks at mixed race and mixed ethnic identity in New Zealand: a unique context, as multiple ethnic identities have been officially recognised for more than 20 years. The book draws upon research across a range of disciplines, exploring historical and contemporary ways in which official and social understandings of mixed race and ethnicity have changed. It focuses on the interactions between race, ethnicity, national identity, indigeneity and culture, especially in terms of visibility and self-defined identity in the New Zealand context. Mana Tangatarua situates New Zealand in the existing international scholarship, positioning experiences from New Zealand within theoretical understandings of mixedness. The chapters develop wider theories of mixed race and mixed ethnic identity, at macro and micro levels, looking at the interconnections between the two. The volume as a whole reveals the diverse ways in which mixed race is experienced and understood, providing a key contribution to the theory and development of mixed race globally."--Provided by publisher.